Insulin resistance and polycystic ovary syndrome through life - Diamanti Kandarakis, Evanthia (2012)
The heterogeneity of Polycystic Ovary Syndrome (PCOS) emphasizes the need for a consensual review of the data concerning its diagnosis and treatment and for determination of the relationship between the development of PCOS and the ethnic origin, the social status and the lifespan. Insulin resistance is an important characteristic in women with PCOS that aggravates features of PCOS. This review is focused in the diagnosis and treatment of insulin resistance and the risk factors for PCOS during childhood, adolescence and postmenopause. The role of endocrine disruptors and/or their interaction with PCOS have also been analyzed.